Rising English Students’ Motivation in Online Learning Platform: Telegram Apps Support - Nur Aisyah, Rasyidah; Istiqomah, Dewi Masitho; Muchlisin, Muhammad (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
This study believes that it needs an effort that encourages students to carry out learning activities to achieve predetermined goals and motivation to determine students' success in the teaching-learning process. The objective of this study is to know the students’ motivation in learning after using e-learning materials using the Telegram app, i.e., telegram bot. This descriptive quantitative research used a closed questionnaire with 11 modified questions, and it was delivered to 46 respondents. Based on analysis of students' learning motivation before using the telegram bot it was highlighted into a good category 80.56%]. This study also manage to reveal three aspects that construct this presents study, namely interests, concerns, and needs. The analysis manage to record that the interesting aspect received 78.19%, the concern aspect received 82.18%, and the need aspect received 81.56%. Thus, and the average score of students' learning motivation was 80.56%. After using the telegram bot, the details of the recapitulation of the motivation questionnaire are as follows, aspects of interest get 84.17%, aspects of attention get 87.23%, aspects of needs get 86.70%, and the average score of student learning motivation is 85.98%. Thus, it can be concluded that the use of telegram bot as e-learning materials can increase student motivation.